Evaluation of sugar cane biochar in the development of Pinus greggii Engelm. ex Parl in forest nursery - Pérez-González, Guadalupe; Hidalgo-Moreno, Claudia; Etchevers-Barra, Jorge D.; de Jong, Ben; Salgado-García, Sergio; Valtierra-Pacheco, Esteban; López-López, Miguel Ángel (REVISTA TERRA LATINOAMERICANA, 2022)
There is a need to replace components of substrates for the development of seedlings in forest nursery, with low-cost products and especially with local and renewable materials. Sugarcane bagasse biochar is lightweight, porous and has a high-water retention capacity. Therefore, the objective of this study was to evaluate the response of biochar based on sugarcane bagasse to produce white pine (Pinus greggii Engelm. ex Parl) plants under nursery conditions. Four treatments were evaluated: (a) biochar with forest soil, (b) forest substrate (composed of 12.5% peat moss, 12.5% agrolite, 25% vermiculite, 50% pine bark), (c) biochar with forest substrate, both in a 1:9 ratio (biochar:soil, biochar:substrate), and (d) forest soil. The effect of fertilization (N, P and K) and biochar on the performance of treatments in soil and forest substrate was evaluated. The growth variables evaluated were plant height, stem diameter, total aerial biomass, total root biomass, aerial/root biomass ratio, and the concentration of accumulated nutrients (N, P, Ca, K, Na and Mg) in the aerial and root parts. The results obtained indicate that as a consequence of the addition of biochar to the soil and fertilization, the height, diameter, biomass (aerial and total) of Pinus greggii were similar to obtained in forest substrate, alone or combined with biochar. These results were associated with the addition of biochar to the soil that increased the absorption of N and its concentration in the aerial biomass, and favored the availability of Mg, Ca, K and P, these last two elements added in fertilization. It is concluded that the combination of biochar and soil in a ratio (1: 9) (p/p) with the addition of fertilizer (N, P and K) can be used in the development of Pinus greggii Engelm ex Parl in the nursery.